Corporate social responsibility and organizational citizenship behavior The mediating role of job satisfaction - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2019)
Purpose The purpose of this paper is to examine the effect of incumbent employees' corporate social responsibility (CSR) perceptions toward multiple stakeholders on their organizational citizenship behavior (OCB) within the context of the tourism and hospitality sector in Turkey. It also aims to examine the mediating role of job satisfaction in these relationships. Design/methodology/approach Data were collected from 215 white-collar employees working full-time in non-managerial positions of hotels and travel services in Istanbul and Antalya regions of Turkey, using a self-administrated questionnaire. The research hypotheses were tested using multiple regression analysis. Findings The result of the study showed that two of the four CSR dimensions, namely, CSR toward society and environment and government, had a significant and positive effect on OCB. On the other hand, CSR toward employee was the only variable among the four dimensions of CSR perception that had a significant and positive effect on employee job satisfaction. The finding of the mediation analysis unfortunately failed to support the mediation effect of job satisfaction on the relationship between CSR perceptions and OCB. Research limitations/implications - The study was limited to the Turkish tourism and hospitality sector. Thus, these findings may not be generalized to other sectors or countries. Future research should consider other sectors both in Turkey and other countries to extend the generalizability of the findings of this study. Practical implications - This paper indicates that employees working in tourism and hospitality sector are highly concerned about their organizational, legal, societal and environmental social activities, which subsequently make them engage in extra role behaviors. Organizations are hereby advised that government law and regulation abiding, society and environmental social activities are very important in the effective functioning of the organizations and improving their service quality, which in turn can help increase their profits and long-term value creation. Originality/value - Scholars in the area of CSR often explore the effect of a single dimension of CSR. Therefore, this paper contributes to the body of literature by examining the effect of employees' CSR perceptions toward multiple stakeholders on employee behavior. Further, it is one of the few papers that highlights the positive effect of legal dimension of CSR on employee behavior within the context of the tourismand hospitality sector.
Keywords: Organizational citizenship behavior; Corporate social responsibility; Job satisfaction; Social identity theory; PERFORMANCE; COMMITMENT; IDENTIFICATION; PERCEPTIONS; INVOLVEMENT; PREDICTORS; EMPLOYEES; INDUSTRY; SYSTEMS; IMPACT